TANTANGAN METODE TARGHIB DAN TARHIB BERDASARKAN AL-QUR'AN DALAM MEMBENTUK KARAKTER GENERASI Z - Pariyal Nadianto; Yelfi Dewi; Merisa; Rahmayanti; Nur Ulfa Rohdi (STKIP Subang, 2024)
This study examines the challenges in implementing the targhib (encouraging) and tarhib (dissuading) methods based on the Qur'an to shape the character of Generation Z. Generation Z, growing up in the digital age with vast access to information, faces various difficulties in developing personalities and character aligned with Islamic values. The targhib and tarhib methods, rooted in Qur'anic teachings, have great potential to foster positive attitudes and prevent negative behaviors among the youth. However, the application of these methods encounters challenges such as shifting social values, the influence of digital technology, and rapid changes in mindset. This study employs a qualitative method with a literature review approach and content analysis of various scholarly sources, including journals, articles, and relevant books. The data are analyzed using thematic analysis techniques to identify key factors and effective strategies for implementing these methods. The findings reveal that the application of targhib and tarhib methods can enhance awareness and positive behavior if conducted with an appropriate approach, including the integration of Islamic values into education and the wise use of digital media. However, the main challenges identified include resistance to change and the need for greater support from family and community environments.